ANALISIS STRATEGI PEMASARAN DENGANMENGGUNAKAN METODE SWOT DAN AHP UNTUKMENINGKATKAN VOLUME PENJUALAN DI PT SIGMAUTAMA - Silvia Alfiana (2020)
In order to survive in increasingly fierce competition outside, companies are required to be able to deal with and deal with this problem by having the right marketing strategy. Therefore PT Sigma Utama is demanded to be able to create the most appropriate marketing strategy by identifying weaknesses, strengths, opportunities, and threats in order to increase sales volume, the most appropriate analytical method used is the SWOT method to identify factors and AHP for determining factors strategy. The results of this study are in the IE matrix the company's position is in cell I (growing and developing), in mapping the SWOT diagram the company's position is in quadrant I (aggressive strategy), the highest weight on alternative corporate strategies is on SO31 (improving production technology) get a weighting of 24%. The strategies that the company can do in accordance with the highest alternative weight, namely improving production technology are: replacing or adding production equipment with more sophisticated technology, maintaining the machine regularly so that the machine is always effective when used, giving tools to the production machine so that the work of the machine is more effective, and equips production equipment.